Biologically Prepared ZnO Nanoparticles for Effective Transparent Sunscreen Applications - Shanmugapriya*, P.; Thanuja, M.Y.; Anusuya, T.; P, V. (Asian Journal of Chemistry, 2013)
Sunscreens are used to provide protection against adverse effects of ultraviolet (UV)B (290-320 nm) and UVA (320-400 nm) radiation. The nanosized ZnO with the features of large volume to area ratio, high ultraviolet absorption and long life-span has been widely used as catalyst, UV absorber in cosmetics and solar cell applications. ZnO belongs to a group of metal oxides, which is characterized by photo catalytic ability and photo-oxidizing capacity against chemical and biological species. Here ZnO nanoparticles have been prepared by using chemical reduction method. Characterization studies such as XRD gives information about crystalline structure and Ultraviolet-visible spectroscopy is used to calculate the absorption peak of the material and Fourier transform infrared spectroscopy describes local environment around ZnO nanoparticles. Photoluminescent activity of biocompatible polymer coated and uncoated ZnO nanoparticles was studied.